Pengaruh Pemberian Variasi Konsentrasi Vitamin B1 (Thiamin HCl) Terhadap Pertumbuhan Fase Vegetatif Anggrek Dendrobium sonia - Hanasari Faida Pranama; M. Anas Dzakiy; Eny Hartadiyati W.H (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to determine the effect of varying concentrations of vitamin B1 on the growth of the vegetative phase of the Dendrobium sonia orchid. This research was carried out experimentally using a Completely Randomized Design (CRD) with 4 treatment levels, namely Growmore Fertilizer (2 gr/l) as a control and vitamin B1 concentration (1 ml/l, 2 ml/l, 3 ml/l) then each -Each treatment was repeated 5 times to get 20 plants, each treatment consisting of 5 plant samples. The parameters used are root length, number of new roots, shoot height and number of shoots. The data obtained was analyzed using the one way anova test. The results of the research showed that Dendrobium sonia orchids treated with varying concentrations of vitamin B1, the parameters of root length, number of shoots, shoot height and average number of shoots had vegetative growth that did not look much different. In conclusion, vitamin B1 has no significant effect on the vegetative growth of Dendrobium sonia orchids. Keywords: Dendrobium sonia, Vegetative Phase, Vitamin B1